Potential of the sector of financial services in view of the socio-economic growth of Ukrainian regions - Mariana Melnyk; Iryna Leshchukh; Мединська Тетяна Володимирівна; Nadiya Rushchyshyn (Institute of Society Transformation (Kyiv, Ukraine & Rzeszow, Poland), 2020)
Nowadays, in the global economy, the sector of financial services is an important mechanism to secure competitiveness. In the first place, it performs the functions of monetary provisions; in the second place, it mobilizes and transforms spare savings into investment resources for extended economic reproduction. Yet, the socio-economic and geopolitical instability in Ukraine has caused a decline in the development of its financial sector, which is confirmed by the rating downgrade of Ukraine in a range of international economic rankings. The purpose of the paper is to provide a complex research of the capacity of the sector of financial services in securing the socio-economic growth of Ukrainian regions. In order to achieve the goal, general and specific research methods were used, including structural and functional, regression-based, factor and system analysis methods of comparison and synthesis. MS Excel was used to visualize and interpret data. The efficiency of the use of the capacity of the sector of financial services in securing the socio-economic growth of regions is evaluated based on the calculation of the related index as an arithmetic average of standardized output parameters that characterize the development of the sector of financial services and socio-economic development of regions. The research has contributed to 1) establishing a high variability of the index of the efficiency of the capacity of the sector of financial services caused by the unequal spatial distribution of the companies in the analyzed sector; 2) verifying a high sensitivity of the sector of financial services to macroeconomic imbalances, fluctuations on global financial and monetary markets, and domestic political crises confirmed by a slight impact of the sector capacity on the pace of gross regional product (GRP) change in Ukrainian regions and the gross valued added (GVA) change in the services sector of the regions; 3) stating a direct correlation between the volume of services provided by financial sector companies and financial solvency of consumers (i.e. residents and businesses), and a direct correlation between the intensity of change in the capacity of the sector of financial services in order to secure the socio-economic growth of regions and employment change in the regions. The fact that a high level of shadow activity is an essential threat to the efficient use of the capacity of the sector of financial services in order to secure the socio-economic growth of Ukrainian regions is emphasized. Unequal spatial distribution of companies within the sector of financial services, imbalance in spatial development of adjoining economy sectors, and credit activity of businesses and population have caused a high variability of the index of the efficiency of the use of the capacity of the sector of financial services in terms of the socio-economic growth in Ukrainian regions. The financial sector of Ukraine is characterized by high sensitivity to fluctuations on domestic and foreign financial and exchange markets that are especially relevant nowadays in view of the coronavirus pandemic. Therefore, forming a comprehensive roadmap activating the mechanisms to improve economic activities in the financial and adjoining markets should be the primary task for public and regional authorities.
Потенціал сектору фінансових послуг у забезпеченні соціально-економічного зростання регіонів України
Economic Annals-XXI, 185(9-10), P. 144-154
Keywords: Sector of Financial Services; Financial and Insurance Activities; Socio-Economic Development of Regions; Shadow Economy; Regional Economy